PENGARUH PERSEPSI KOMUNIKASI PEMASARAN TERPADU TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KUROGI - Bulandari, Devita; Manalu, S.Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
As the capital of the province of Central Java, restaurant growth in Semarang has increased annually. The trend of increasing the number of restaurants and restaurants in the city of Semarang shows that in 2016 rose 43 units to 345 restaurants and restaurants (BPS, 2016). KUROGI as one of the restaurant businesses in Semarang used two types of marketing mix namely interactive marketing through Instagram and sales promotion to reach its target. Despite the high engagement from KUROGI's official Instagram, data showed a decrease in the number of sales. The decline began to occur from January 2019 to June 2019. This income is far from the KUROGI target of Rp. 15,000,000 sales per day. Therefore this thesis tries to explain whether there is an influence of perception of integrated marketing communication on purchasing decisions of KUROGI's consumer. Theories that used in this thesis are The Yale information processing model,AIDA Theory and Prospect Theory. The sampling technique used in this study is a non-random sampling technique specifically purposive sampling consists of 100 samples. Testing is done by using Linear Regression Test and Logistic Regression Test. The results showed that there was an influence of interactive marketing perceptions of brand awareness found significance results of 0.00 1.98472. While the perception of sales promotion variables did not affect brand awareness showed a significance value of 0.460> 0.05 and t value of 0.741 1.98447. Thus, interactive marketing variables can influence purchasing decisions with and without mediation by brand awareness variables and sales promotion variables can directly influence purchasing decisions. Both the AIDA Theory and Prospect Theory can be the basis for explaining how the influence of the variable integrated marketing communication affects purchasing decisions directly or indirectly.